Development of managerial economics as a component of economic theory - Ostapenko, Tetiana (Technology audit and production reserves (Online), 2024)
The object of research is managerial economics, which is considered as a component of economic theory. The scientific problem is that there are such concepts as management and managerial economics, which are tangential and somewhat overlapping. Managerial economics is included in the structure of the economic system as a separate component. It is also proven that managerial economics is a systemic entity and has the following levels: global, macro-, meso-, micro- and nano-. The study defined these levels and outlined the use of the global (international) and macro levels. Analysis of these categories is necessary for understanding the governance and governance conditions of global and national economies. The essence of the obtained results is that the existing system of managing international relations is inflexible and difficult to solve the global problems of humanity. And the management of national economies must correspond to the strategic development plans of a particular nation. These obtained results can be explained by the immobility of management structures and the need to revise the global economic order. At the state level, there should be levers for regulating economic relations. It was noted in the work that society is a set of people united at a certain stage of historical development by one or another economic relations that determine all other social relations. The economic life of society consists of various phenomena and processes, the essence of which must be sought in social production. The concept of «managerial economics» is often used to characterize the regulation of social production. There are different approaches to defining the content of managerial economics. First, managerial economy is considered as regulation by a set of industries and types of material production. Secondly, a system of regulation of productive forces and production relations is usually associated with managerial economics. Thirdly, managerial economics regulates the conditions for achieving equilibrium and cyclicality of social production. Об’єктом дослідження є управлінська економіка, що розглядається як складова економічної теорії. Науковою проблемою є те, що існують такі поняття, як управління та управлінська економіка, які є дотичними та дещо перетинаються. Управлінська економіка включається до структури економічної системи як окрема складова. Також засвідчено, що управлінська економіка є системним утворенням та має такі рівні: глобальний, макро-, мезо-, мікро- та нано-. У дослідженні проведено визначення цих рівнів та було окреслено використання глобального (міжнародного) та макрорівня. Аналіз цих категорій необхідний для розуміння управління та умов керованості глобальної та національної економік. Сутність отриманих результатів полягає у тому, що існуюча система керування міжнародними відносинами є негнучкою та важкою для вирішення глобальних проблем людства. А управління національними економіками має відповідати стратегічним планам розвитку тієї чи іншої нації. Ці отримані результати можуть бути пояснені немобільністю управлінських структур та потребою перегляду всесвітнього економічного порядку. На рівні держави мають бути важелі для регулювання економічних відносин. В роботі було зауважено, що суспільство являє собою сукупність людей, об’єднаних на певному ступені історичного розвитку одними чи іншими економічними відносинами, що визначають всі інші суспільні відносини. Економічні життя суспільства складається з різноманітних явищ та процесів, сутність яких необхідно шукати у суспільному виробництві. Поняття «управлінська економіка» часто використовується для характеристики регулювання суспільного виробництва. Існують різні підходи до визначення змісту управлінської економіки. По-перше, управлінська економіка розглядається як регулювання сукупністю галузей та видами матеріального виробництва. По-друге, з управлінською економікою зазвичай асоціюється система регулювання продуктивними силами та виробничими відносинами. По-третє, управлінська економіка регулює умови досягнення рівноваги та циклічності суспільного виробництва.